Persepsi Dosen Dalam Penerapan Konsep Pendidikan Merdeka Belajar - Faisal Rafandra; Fattah Xaquil (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
In the government regulation referred to in Article 91 paragraph (1), which states that every education unit on formal and non-formal pathways is required to carry out education quality assurance, while Article 91 paragraph (3) states that education quality assurance aims to meet or exceed the National Education Standards. .